Multi-center nationwide study on pediatric psychiatric inpatients 2000-2018: length of stay, recurrent hospitalization, functioning level, suicidality, violence and diagnostic profiles - Kronström Kim; Tiiri Elina; Vuori Miika; Ellilä Heikki; Kaljonen Anne; Sourander Andre (SPRINGER, 2022)
Inpatient treatment is an important part of child and adolescent psychiatric (CAP) care. This nationwide study explores the changes in length of stay, recurrent hospitalization, functioning level, suicidality, violence and diagnoses of CAP inpatients in Finland in 2000, 2011 and 2018. We obtained comprehensive questionnaire data on each study year from 93 to 95% of all CAP wards in Finland. We split the 1276 inpatients into two age groups in each study year: under 13 and 13-18. The median length of stay in inpatient treatment decreased from 82.0 days in 2000 to 20.5 days in 2018 (p < 0.001) and recurrent hospitalization increased from 38 to 46%. General functioning, which was evaluated by the Children's Global Assessment Scale, deteriorated by an average of six points between 2000 and 2018. Violent threats decreased from 21.5 to 16.6% and violent acts decreased from 26.9 to 20.3%. Suicidal threats decreased from 42.6 to 23.3% in those aged under 13 and remained stable among those aged 13-18. In the 13-18 group, there was an increase in the diagnoses of ADHD, from 5.0 to 16.9% and depression, from 25.1 to 41.7%. However, psychosis decreased from 23.2 to 12.6% in the older age group. In the whole cohort, anxiety disorders increased from 7.6 to 15.6%. The overall picture does not show that CAP inpatients have become more disturbed. While the general functioning of CAP inpatients deteriorated somewhat over the 2000-2018 study period, symptoms of suicidality and violence remained stable or decreased. There was also a continuous increase in short-term treatment.